BS ISO 23906-2. Cigarettes. Determination of benzo[a]pyrene in cigarette mainstream smoke with an intense smoking regime using GC/MS. Part 2. Method using cyclohexane as extraction solvent (25th March 2022) - British Standards Institution,
No abstract available